CP-sensitive observables for the process pp → Z → ZH → 2e2μ. (December 2020) - Belyaev, N; Konoplich, R; Prokofiev, K; Reese, S
Abstract: After the discovery of the Higgs boson at the LHC, additional precise measurements were performed testing its compatibility with the Standard Model (SM). One of the most important deviations from the SM predictions is the possible CP violation in the Higgs sector that may have implications for the origin of the baryon asymmetry in the early Universe. In this paper, new kinematic observables are suggested to probe the CP properties of the Higgs boson. The Higgs boson associated production with a Z boson with a four-lepton final state is studied at theoretical and Monte Carlo levels. Sensitivity of considered observables to the CP nature of the Higgs boson is demonstrated.